Sampling Constraints and Variability in the Analysis of Bacterial Community Structures in the Sea Surface Microlayer - Wong, Shu-Kuan; Suzuki, Shotaro; Cui, Yingshun; Kaneko, Ryo; Kogure, Kazuhiro; Hamasaki, Koji (Frontiers in Marine Science, 2021)
The sea surface microlayer (SML) is a thin surface film located at the interface between oceans and the atmosphere. In this study, three SML samplers—polycarbonate membrane (PC), glass plate (GP), and drum sampler (DS)—were used to collect microbiological DNA samples for molecular analysis. Among the three samplers, DS only took half the time to sample the SML compared to GP while PC were able to sample the thinnest SML depth. Biological matter and distinct bacterial communities in the SML were apparent during low wind conditions in samples collected by three samplers. Signs of biological matter [transparent exopolymer particles (TEP) and chlorophyll-a concentrations] depletion, and an increased similarity in the biological communities of the SML and underlying water (UW), were more pronounced during high wind speed conditions in samples collected by GP and DS. GP samples had lower biological matter enrichment than DS samples compared with UW. The depletion of biological matter in GP samples were more apparent during periods of high chl-a concentrations in the SML. In contrast, PC was able to consistently sample an SML community distinct from that of the UW, regardless of wind conditions. Bacterial community DNA samples obtained by the three SML samplers showed relatively consistent patterns of community structure, despite large fluctuations between seasons (summer vs. winter) and layers (SML vs. UW) being observed. Although no SML-specific taxon was detected in this study, a comparison of the representation of taxonomic groups in each sample suggested that certain taxa (15 orders) were specifically enriched or depleted in the SML, especially taxa belonging to Actinobacteria, Cyanobacteria, Deferribacteria, and Proteobacteria. This trend was consistent regardless of sampling method, implying that these bacterial groups are key taxa in the biogeochemical processes occurring at the air-sea interface.